The Influence of Jigsaw Cooperative Model toward Writing Exposition Text Ability of Class X At SMK Negeri 1 Pematang Siantar - Nasution, Tuti Ariani; Purba, Anita; Afrinda, Vobi (Budapest International Research and Critics University, 2020)
The purpose of this study is: (1) To know that Jigsaw Cooperative Model can improve the students’ writing Exposition ability and (2) to describe the process ofJigsaw Cooperative Model in improving students’ writing Exposition ability. This study was conducted at class X at SMK Negeri 1 Pematang Siantar.The population were 70 students. The qauntitative data were taken from the scores of the pre-test and post-test. The total score is 4894, the mean 69, 9 thus, in the post test found the total score is 5981, and the mean 85, 4.Jigsaw Cooperative Model inspired both the students and the studyer in improving the ability of English especially on writing. The students could practice their skill of English in the different situation and treatment. They could express their idea or opinion freely as the studyer only became mediator during the activities of Jigsaw Cooperative Model as it was student-centred. In fact, the students’ cooperation increased. They helped each other, communicated using English, and built the idea, imagination and opinion that they wanted to compose in their writing during applying Jigsaw Cooperative Model.